Pullulan/poly(N-vinylimidazole) cryogel: An efficient adsorbent for methyl orange - Hezarkhani, Marjan; Usturk, Selma; Ozbilenler, Cahit; Yilmaz, Elvan (Wiley, 2021)
Pullulan/poly(N-vinylimidazole) (PNVI) hybrid cryogels were synthesized under free radical polymerization and chemical crosslinking conditions in an alkaline, aqueous solution of pullulan (PUL), N-vinylimidazole (NVI), ammonium persulfate and epicholorohydrin (ECH) at -18 degrees C. PUL and PNVI cryogels alone were also synthesized under similar conditions. Optimum cryogel formation conditions were determined by considering product yields and gel fractions of the samples. The products were characterized by elemental analysis, FTIR-ATR spectrometry, Thermal gravimetric analysis, and scanning electron microscopy (SEM) analyses. It has been found that PUL/PNVI hybrid samples bear improved physicochemical properties compared to ECH crosslinked PUL and PNVI samples alone. They act as hydrogels in aqueous medium reaching equilibrium swelling capacity values of the order of 600%. Dried PUL/PNVI cryogels show higher thermal stability than the dried cryogels of the parent polymers and maintain their physical integrity over a prolonged time period. Macroporous morphology was revealed by SEM analysis. Having 54.2 mg/g maximum equilibrium adsorption capacity in 200 ppm methyl orange solution and maintaining 95% of its adsorption capacity at the end of seven consecutive adsorption/desorption cycles, PUL/PNVI cryogel proved to be an efficient and durable dye adsorbent using methyl orange as the model compound in aqueous solution.
Keywords: adsorption; biopolymers and renewable polymers; crosslinking; gels; radical polymerization